The optimization of welding parameters for friction stir spot welding of high density polyethylene sheets - KURTULMUŞ, MEMDUH; BİLİCİ, MUSTAFA KEMAL (ELSEVIER SCI LTD, 2011)
Friction stir spot welding parameters affect the weld strength of thermoplastics, such as high density polyethylene (HDPE) sheets. The strength of a friction stir spot weld is usually determined by a lap-shear test. For maximizing the weld strength, the selection of welding parameters is very important. This paper presents an application of Taguchi method to friction stir spot welding strength of HOPE sheets. An orthogonal array, the signal to noise ratio (S/N), and the analysis of variance (ANOVA) are employed to /investigate friction stir welding parameter effects on the weld strength. From the ANOVA and the S/N ratio response graphs, the significant parameters and the optimal combination level of welding parameters were obtained. Experimental results confirmed the effectiveness of the method. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: AUTOMOTIVE APPLICATIONS; STAINLESS-STEEL; TAGUCHI METHOD; TOOL; PERFORMANCE; ALLOYS; DESIGN